![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1:
a, \(\sqrt{50.98} = 5\sqrt{2} . 7\sqrt{2} = 70\)
b, \(\sqrt{2,5.12,1} = 30,25\)
c, \(\sqrt{17.51.27} = \sqrt{23409} = 153\)
d, \(\sqrt{32.128} = \sqrt{4096} = 64\)
e, \(\sqrt{3,2.7,2.49} = 7\sqrt{3,2.7,2} = 7\sqrt{23,04} =33,6\)
g, \(\sqrt{2,5.12,5.20} = \sqrt{625} = 25\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{\sqrt{2}}{\sqrt{18}}=\dfrac{1}{3}\)
b) \(\dfrac{\sqrt{15}}{\sqrt{735}}=\dfrac{1}{7}\)
c) \(\dfrac{\sqrt{12500}}{\sqrt{500}}=\dfrac{50\sqrt{5}}{10\sqrt{5}}=\dfrac{50}{10}=5\)
d) \(\dfrac{\sqrt{6^5}}{\sqrt{2^33^5}}=\dfrac{36\sqrt{6}}{18\sqrt{6}}=\dfrac{36}{18}=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a\)
\(\sqrt{2,7}\)\(.\)\(\sqrt{1,2}\)
\(=\)\(\sqrt{2,7.1,2}\)
\(=\)\(\sqrt{3,24}\)
\(=\)\(1,8\)
\(b\)
\(\sqrt{85}.\sqrt{125}.\sqrt{68}\)
\(=\)\(\sqrt{85.125.68}\)
\(=\)\(\sqrt{722500}\)
\(=\)\(850\)
\(c\)
\(\frac{\sqrt{13,5}}{\sqrt{4,5}}\)
\(=\)\(\frac{3,67}{2,12}\)
HỌC TỐT!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\sqrt{3+2\sqrt{2}}-\sqrt{3-2\sqrt{2}}=\sqrt{2}+1-\left(\sqrt{2}-1\right)=2\)
b) \(\dfrac{1}{\sqrt{3}-1}-\dfrac{1}{\sqrt{3}+1}=\dfrac{\sqrt{3}+1-\left(\sqrt{3}-1\right)}{3-1}=1\)
c) \(2\sqrt{5}-3\sqrt{45}+\sqrt{500}=2\sqrt{5}-9\sqrt{5}+10\sqrt{5}=3\sqrt{5}\)
d) \(\dfrac{1}{\sqrt{3}+\sqrt{2}}-\dfrac{\sqrt{15}-\sqrt{12}}{\sqrt{5}-2}=\dfrac{1}{\sqrt{3}+\sqrt{2}}-\dfrac{\sqrt{3}\left(\sqrt{5}-\sqrt{4}\right)}{\sqrt{5}-2}=\dfrac{1}{\sqrt{3}+\sqrt{2}}-\sqrt{3}=\dfrac{1-\sqrt{3}\left(\sqrt{3}+\sqrt{2}\right)}{\sqrt{3}+\sqrt{2}}=\dfrac{1-3-\sqrt{6}}{\sqrt{3}+\sqrt{2}}=\dfrac{-2-\sqrt{6}}{\sqrt{3}+\sqrt{2}}=\dfrac{-\sqrt{2}\left(\sqrt{3}+\sqrt{2}\right)}{\sqrt{3}+\sqrt{2}}=-\sqrt{2}\)
e) \(\dfrac{1}{2+\sqrt{3}}-\dfrac{1}{2-\sqrt{3}}+5\sqrt{3}=\dfrac{2-\sqrt{3}-\left(2+\sqrt{3}\right)}{4-3}+5\sqrt{3}=-2\sqrt{3}+5\sqrt{3}=3\sqrt{3}\)
f) \(\sqrt{3}-\sqrt{4+2\sqrt{3}}=\sqrt{3}-\left(\sqrt{3}+1\right)=-1\)
g) \(\dfrac{5-\sqrt{5}}{\sqrt{5}-1}-\dfrac{4}{\sqrt{5}+1}=\dfrac{\sqrt{5}\left(\sqrt{5}-1\right)}{\sqrt{5}-1}-\dfrac{4}{\sqrt{5}+1}=\sqrt{5}-\dfrac{4}{\sqrt{5}+1}=\dfrac{5+\sqrt{5}-4}{\sqrt{5}+1}=1\)
h)\(\sqrt{37-20\sqrt{3}+\sqrt{37+20\sqrt{3}}}=\sqrt{37-20\sqrt{3}+\left(5+2\sqrt{3}\right)}=\sqrt{42-18\sqrt{3}}=\sqrt{\left(3\sqrt{3}+3\right)^2+6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a: \(=\sqrt{32.4}=\dfrac{9}{5}\sqrt{10}\)
b: \(=\sqrt{5\cdot5\cdot7\cdot7\cdot11\cdot11}=5\cdot7\cdot11=385\)
c: \(=5-2\sqrt{6}\)
d: \(=18-1=17\)
e: \(=3\sqrt{2}-2\sqrt{3}+7\sqrt{3}-7\sqrt{2}=-4\sqrt{2}+5\sqrt{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=2\sqrt{3}-9\sqrt{3}+5\sqrt{3}=-2\sqrt{3}\)
\(b,=-1-4\sqrt{5}-2-12\sqrt{11}+10\sqrt{5}\)
\(=-3-4\sqrt{5}-12\sqrt{11}+10\sqrt{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(=\left(\dfrac{4}{3}\sqrt{3}+\sqrt{2}+\sqrt{\dfrac{10}{3}}\right)\cdot\left(\sqrt{\dfrac{6}{5}}+\sqrt{2}-\dfrac{4}{\sqrt{5}}\right)\)
\(=\left(\dfrac{4\sqrt{3}}{3}+\dfrac{3\sqrt{2}}{3}+\dfrac{\sqrt{30}}{3}\right)\cdot\left(\dfrac{\sqrt{30}}{5}+\dfrac{5\sqrt{2}}{5}-\dfrac{4\sqrt{5}}{5}\right)\)
\(=\dfrac{\left(4\sqrt{3}+3\sqrt{2}+\sqrt{30}\right)\left(\sqrt{30}+5\sqrt{2}-4\sqrt{5}\right)}{15}\)
2: \(=\left(2\sqrt{3}+6\sqrt{3}\right)\cdot\dfrac{\sqrt{3}}{2}-5\sqrt{6}\)
\(=\dfrac{8\sqrt{9}}{2}-5\sqrt{6}=4\sqrt{9}-5\sqrt{6}=12-5\sqrt{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\sqrt{3^2.5}=\sqrt{45}\)
\(b,1,2\sqrt{5}=\sqrt{1,2^2}.\sqrt{5}=\sqrt{1,44.5}=\sqrt{7,2}\)
\(c,ab^4\sqrt{a}=\sqrt{a^2b^8a}=\sqrt{a^3b^8}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a.\(\dfrac{\sqrt{2}}{\sqrt{18}}=\sqrt{\dfrac{2}{18}}=\sqrt{\dfrac{1}{9}}=\dfrac{1}{3}\)
b.\(\dfrac{\sqrt{15}}{\sqrt{735}}=\sqrt{\dfrac{15}{735}}=\sqrt{\dfrac{1}{49}}=\dfrac{1}{7}\)
c.\(\dfrac{\sqrt{12500}}{\sqrt{500}}=\sqrt{\dfrac{12500}{500}}=\sqrt{25}=5\)
d.\(\dfrac{\sqrt{6^5}}{\sqrt{2^3.33^5}}=\sqrt{\dfrac{2^5.3^5}{2^3.3^5}}=\sqrt{2^2}=2\)
\(\sqrt{1.5}\sqrt{1.2}\sqrt{500}\)
\(=\sqrt{900}\)
\(=30\)
\(\sqrt{1,5}\cdot\sqrt{1,2}\cdot\sqrt{500}=\sqrt{1,5\cdot1,2\cdot500}\)
\(=\sqrt{900}=30\)